2021
DOI: 10.3390/jcm10020325
|View full text |Cite
|
Sign up to set email alerts
|

Aorto-Iliac Artery Calcification and Graft Outcomes in Kidney Transplant Recipients

Abstract: While the association of vascular calcification with inferior patient outcomes in kidney transplant recipients is well-established, the association with graft outcomes has received less attention. With this dual-centre cohort study, we aimed to determine the clinical impact of recipient pre-transplant aorto-iliac calcification, measured on non-contrast enhanced computed tomography (CT)-imaging within three years prior to transplantation (2005–2018). We included 547 patients (61.4% male, age 60 (interquartile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…This prospective cohort study found no direct association between AIC and eGFR after transplant. The results from this study are in line with earlier studies who did not find an association between AIC and post-transplant graft function (11)(12)(13)(14)16). However, we found a significant interaction between time and ipsilateral calcification score, indicating that patients with a higher calcification score had a lower eGFR trajectory during the follow-up time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This prospective cohort study found no direct association between AIC and eGFR after transplant. The results from this study are in line with earlier studies who did not find an association between AIC and post-transplant graft function (11)(12)(13)(14)16). However, we found a significant interaction between time and ipsilateral calcification score, indicating that patients with a higher calcification score had a lower eGFR trajectory during the follow-up time.…”
Section: Discussionsupporting
confidence: 91%
“…Current studies that investigated the relationship between AIC and graft function have several limitations, from which the most important ones are a retrospective design, a subjective quantification method of aorto-iliac vascular disease which limits generalizability and the use of statistical methods that do not account for drop-out (10)(11)(12)(13)(14)(15)(16). To address these issues, we performed a prospective cohort study in which all patients underwent non-contrast-enhanced CT-scan for objective, quantitative assessment of AIC using an adaptation of the Agatston score.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies did not have a unified reporting of the abdominal calcification and were based on different assessment modalities. Benjamens et al showed similar results with overall decrease survival among kidney transplant recipients when they have significant arterial calcifications [7,30]. In our study, we were able to correlate the AAC value, in addition to survival, with the abnormal pulse pressure and the decreased iothalamate clearance as clinical and laboratory markers for overall survival.…”
Section: Discussionsupporting
confidence: 78%
“…Ichii et al arrived at the statistically independent association between lower eGFR and the quantitative degree of aortic calcification in non-dialysis patients [17]. Moreover, in 2021, Benjamens et al demonstrated that pre-transplant aorto-iliac calcification is associated with 1-year eGFR in univariate linear regression analyses [23]. Tatami et al identified trends between abdominal aortic calcifications and cardiovascular events in asymptomatic non-dialysis patients (median eGFR, 43.2 + 17.7 mL/min/1.73 m 2 ) [24].…”
Section: Discussionmentioning
confidence: 99%